Case Study: Giant Cell Arteritis with Vertebral Artery Stenosis - Daniel Chomlak, R. (Clin Med Insights Arthritis Musculoskelet Disord, 2016)
In giant cell arteritis (GCA), involvement of the vertebral arteries is rare with reported rates of 3%–4% for ischemic events secondary to vertebral artery stenosis or occlusion for those patients with GCA. This case study describes a patient who initially presented with acute onset of vertigo but was also found to have transient, side-alternating upper limb neurological findings. While initial imaging showed no vascular abnormalities, it was not until GCA was eventually confirmed with a temporal artery biopsy that the initial scans were shown to have bilateral narrowing of the vertebral arteries. While rare, vertebral artery involvement is an important complication to consider in the setting of GCA due to the high rate of associated mortality, despite immunosuppressive therapy.